2010
DOI: 10.3109/15376516.2010.482962
|View full text |Cite
|
Sign up to set email alerts
|

Micronuclei frequencies in peripheral blood and buccal exfoliated cells of young smokers and non-smokers

Abstract: Cytogenetic biomarkers, such as micronuclei in peripheral blood or oral mucosa, are widely used for evaluation of exposure to genotoxins or carcinogens. Tobacco is one of the strongest carcinogens, responsible for development of different types of cancers. The aim of this study was to assess the genotoxicity of cigarette consumption in young smokers and to correlate results of cytogenetic analysis in peripheral blood lymphocytes and exfoliated buccal cells. The study was conducted on samples taken from 43 smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 40 publications
5
24
1
Order By: Relevance
“…Their predictive aspect for cancer risk assessment at a group level, especially of micronuclei (12) and chromosomal aberrations (28), is highly important. Our results indicate that higher frequency of chromatid and total structural aberrations are most likely related to cigarette smoking and are in agreement with previously reported results for micronuclei frequencies (22). Other analyses of micronuclei frequencies in Bosnian population also revealed the negative impact of cigarette smoking on genetic material (29,30).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Their predictive aspect for cancer risk assessment at a group level, especially of micronuclei (12) and chromosomal aberrations (28), is highly important. Our results indicate that higher frequency of chromatid and total structural aberrations are most likely related to cigarette smoking and are in agreement with previously reported results for micronuclei frequencies (22). Other analyses of micronuclei frequencies in Bosnian population also revealed the negative impact of cigarette smoking on genetic material (29,30).…”
Section: Discussionsupporting
confidence: 82%
“…Mainstream cigarette smoke also caused an elevation of bulky DNA adducts, oxidative DNA damage, and an extensive downregulation of microRNAs in lung (21). In our previous study conducted in Bosnia and Herzegovina, cigarette consumption increased the micronuclei frequency in peripheral blood lymphocytes in group of young smokers (22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of smoking on the presence of MN and NA in buccal mucosa cells has been a controversial topic, because some authors have found no relationship, whereas others found an association [10,55,[56][57][58][59][60][61][62]. Some authors have considered diet and the number and type of cigarettes smoked per day (packs per year, with or without filters, regular or light, type and origin of snuff) [55,61,63], but results have been variable.…”
Section: Smokingmentioning
confidence: 99%
“…In relation to smoking habits and the number of MN, the reports are very controversial, some authors described that smoking increased the frequency of MN [27][28][29][30] and other authors did not observe this effect. [31][32][33][34] In this study, the smoking habit was similar between the studied groups, and there was no correlation between the number of MN and number of individuals who smoke (table III).…”
Section: Dna Damages In Mexican Nativesmentioning
confidence: 99%